Efficacy of 90Yttrium‐ibritumomab tiuxetan in relapsed/refractory extranodal marginal‐zone lymphoma. Issue 1 (20th May 2013) - Vanazzi, Anna; Grana, Chiara; Crosta, Cristiano; Pruneri, Giancarlo; Rizzo, Stefania; Radice, Davide; Pinto, Antonello; Calabrese, Liliana; Paganelli, Giovanni; Martinelli, Giovanni
Abstract We evaluated clinical activity of 90Yttrium‐ibritumomab (90Y‐ibritumomab) tiuxetan in extranodal marginal‐zone lymphoma. From May 2004 to April 2011, 30 patients affected by relapsed/refractory marginal‐zone lymphoma—arisen at any extranodal site—received 90Y‐ibritumomab tiuxetan at the activity of 0.4 mCi/kg. Median age was 57 years. At time of treatment, 13 out of 30 patients had disseminated disease (stage III/IV). All patients had received a previous treatment with a maximum of 7. Overall response rate was 90%: 23 patients achieved a complete response (77%); partial response occurred in 4 patients (13%), stable disease in 2 patients (7%) and 1 progression (3%). With a median follow‐up of 5.3 years, median time to relapse was not reached; 2 patients relapsed after complete response; 18 out of 23 complete responses are still responders after >3 years, 12 of them after >5 years. 90Y‐ibritumomab tiuxetan seems to be active in patients with extranodal marginal‐zone lymphoma relapsed/refractory to conventional treatment including radiotherapy. These results suggest that radioimmunotherapy could represent a possible option for the treatment in this subset of patients. Copyright © 2013 John Wiley & Sons, Ltd.